Comparison of multiple flatfoot indicators in 5–8-year-old children - Žukauskas Saidas (De Gruyter, 2021)
The foot posture is age dependent. The purpose of this study was to investigate the relationship between the 6-item version of the foot posture index (FPI) and other clinical, foot anthropometric, radiological measurements for the foot position in 5–8-year-old children.